Interactions of Potent A. Comosus Compounds with Thromboxane A2 Receptor: a Molecular Docking and Pharmacokinetic/Toxicity Prediction Study - Hasan, Rahmawaty (Proceeding International Conference on Religion, Science and Education, 2026)
Thromboxane A2 (TxA2) is a key signaling molecule involved in cardiovascular disease, promoting platelet aggregation, vasoconstriction, and cell proliferation. TxA2 may trigger cell proliferation in arterial walls, thereby contributing to atherosclerosis. Prior studies show that A. comosus is likely to be beneficial to the cardiovascular system by protecting cell membrane integrity and enhancing cardiac systolic and diastolic function. Using molecular docking, the target proteins of potent A. comosus chemical compounds with pharmacological activity can be precisely predicted and identified based on ligand-protein interaction scores and models generated by AutoDock 4.2 in AutoDock Tools. The results revealed that Hydroxysitosterol, 5alpha,8alpha-Epidioxyergosta-6,22-dien-3beta-ol, and N,N’-Bis(4-hydroxy-3-methoxycinnamoyl)-1,4-butanediamine can be potential compounds from A. comosus with alternating cardiovascular disease based on binding energy values and TxA2 inhibition interactions. These potential compounds can inhibit the activity of TxA2 by interacting with energy values of -11.35, -10.33, and -9.21 kcal/mol. Pharmacokinetic predictions revealed that the potential compounds are absorbed in the intestine, exhibit strong plasma protein binding, and are inhibitors of CYP3A4 and CYP2C9. Prediction of toxicity reveals that the potential compounds fall into the class of drug-induced acute liver failure with medium carcinogenic risk. 7alpha-Hydroxysitosterol, N,N’-Bis(4-hydroxy-3-methoxycinnamoyl)-1,4butanediamine, and 5alpha,8alpha-Epidioxyergosta-6,22-dien-3beta-ol are good lead compounds to synthesize as an alternative inhibitor of TxA2